Miller-Fisher syndrome in association with enterovirus infection - Moustaki, Maria; Gika, Artemis; Fretzayas, Andrew M.; Voutsioti, Aikaterini; Yiallouros, Panayiotis K.; Karpathios, Themistocles (My University, 2012)
Miller-Fisher is a rare syndrome of childhood that presents with external ophthalmoplegia, ataxia, and areflexia. It has been mainly associated with a preceding Campylobacter infection and less commonly with other bacterial or viral infections. This report describes, for the first time, a child with Miller-Fisher syndrome and documented Enterovirus infection, as it was proven by the isolation of Enterovirus from cerebrospinal fluid by polymerase chain reaction testing.
Keywords: Antiganglioside antibodies; Enterovirus; Miller-Fisher syndrome